Evaluation of a model for teaching analogies in secondary science. - Harrison, Allan G. (Curtin University, 1992)
Analogies have long been tools of discovery in mathematics and science, and are often used in the classroom as explanatory devices to help students understand difficult science concepts. However, research has shown that for many students, analogies engender misconceptions rather than scientists' science. It is believed that misconceptions arise when students reconstruct their knowledge within the context of their prior conceptions, and that misconceptions arise whenever the student has a different conception of the analog to the teacher or the student applies the analogy beyond its limits.The literature is richly endowed with descriptions of how it is thought that analogies generate meaning and contain a range of suggestions for improving classroom pedagogy when analogies are used. Five teaching models have been identified which claim to improve analogical instruction, and one of these, the teaching-with-analogies (TWA) model (Glynn, 1989) has been modified at the Science and Mathematics Education Centre of Curtin University for use in secondary science classrooms. To date, no empirical studies have been performed to determine the efficacy of this modified TWA model.This study set out to evaluate the modified TWA model in a qualitative interpretive manner by observing teachers, who had been in-serviced about the model, using analogies in their lessons. Data were generated from the verbatim transcripts of each teacher's in-class performance, each teacher's post-lesson interview and interviews with a number of the students who received the analogical instruction. The emergent data were interpreted from a constructivist perspective with attention being given to credibility, dependability and confirmability.The data derived from one teacher teaching four analogies to Year 8 and 10 science students were reported in this thesis. Three of these analogies were taught using the modified TWA model and these analogies were, light waves are like water waves, conduction of heat in a solid is like the domino effect and the refraction of light as it passes from air into perspex is like a pair of wheels rolling from a smooth surface onto a rough surface. The fourth analogy in which the size of a mole was illustrated using three brief analogies was reported only briefly because the teacher failed to use the modified TWA model during this lesson.The study's findings demonstrated that student understanding of difficult science concepts did appear to be enhanced by the use of the modified TWA model when analogies were included in the lesson. For analogies to be effective, it is believed that two teacher activities are essential: firstly, ensuring that the students understand the analog in the same way as the teacher and secondly, that the unshared attributes of the analogy are highlighted during the lesson. It is also asserted that an exemplary teacher, teaching-in-field, can integrate the modified TWA model into her teaching if she is provided with peer support over at least three to four uses of the model during normal lessons. It appears that maintenance of the TWA model within a teacher's pedagogy requires a supportive colleague to provide critical feedback and encouragement.This study raised some important questions that should be addressed in future research on the use of the modified TWA model. Can the modified TWA model produce conceptual change where alternative student conceptions are firmly entrenched? Can the modified TWA model be incorporated into the pedagogy of most teachers? Is there a more appropriate model for teaching-with-analogies?